2012
DOI: 10.5121/ijpla.2012.2401
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Bacterial Foraging Algorithm For Solving Job Shop Scheduling Problems

Abstract: Bio-Inspired computing is the subset of Nature-Inspired computing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…Biological studies have shown that the foraging process includes four steps as shown in Figure 3 which includes swarming, reproduction and elimination-dispersal (Tang et al, 2006). The E-coli bacteria can have its movement as a 'run' which is moving in a particular direction whereas a 'tumble' denotes that E-coli can change its direction (Narendhar and Amudha, 2012;Panigrahi et al, 2011;Passino, 2002;Kim et al, 2007).…”
Section: Conceptual Representationmentioning
confidence: 99%
“…Biological studies have shown that the foraging process includes four steps as shown in Figure 3 which includes swarming, reproduction and elimination-dispersal (Tang et al, 2006). The E-coli bacteria can have its movement as a 'run' which is moving in a particular direction whereas a 'tumble' denotes that E-coli can change its direction (Narendhar and Amudha, 2012;Panigrahi et al, 2011;Passino, 2002;Kim et al, 2007).…”
Section: Conceptual Representationmentioning
confidence: 99%
“…In order to explore separately the local and global search proprieties of BFOA, researchers hybridized it with other algorithms, applied it to several real world problems and proved its effectiveness over many works, e.g., mathematical modeling for solving simultaneous equation problems [19], solving scheduling problems [12], mechanical problems [2], solar PV modeling [20], and numerical optimization [1]. More hybridization is observed in [18,21].…”
Section: Related Workmentioning
confidence: 99%
“…In this way, appliances' waiting time is minimized, and UC is achieved maximally. This is the multi-objective problem; several authors handle it using different approaches, as mentioned in the literature [12][13][14][15][16][17]. Here, it is handled by the metaheuristics for scheduling the residential area loads in order to reduce the electricity cost and maximize the UC.…”
Section: Uc Maximizationmentioning
confidence: 99%
“…In the literature, many DSM techniques are proposed [8][9][10][11] to achieve the aforementioned objectives. However, UC is not considered in most of these techniques, like [8,10,[12][13][14][15][16][17]. In these works, [11,18,19] aim to reduce the electricity cost, and [20,21] focus on minimizing the aggregated power consumption using integer linear programming and mixed integer linear programming.…”
Section: Introductionmentioning
confidence: 99%